Supervisi Pendidikan Sebagai Upaya Meningkatkan Kinerja Guru Pada Sekolah SMP Swasta PAB 1 Medan Estate - Fitra Amalia Harahap; Era Yunita; Tri Suci Apriani Harahap; Wardah Sahrani Sibarani; Akbar Rafsanjani; Fauzan Azhima Sirait (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This study aims to find out and Identify the extent of the influence of educational supervision on teacher performance at PAB 1 Medan Estate Private Junior High School. Efforts to improve quality Education needs to be done gradually with reference to the strategic plan. Involvement of all components of education (teachers, principals, communities, committees schools, boards of education, and institutions) through good planning and realize the launched educational program. The supervision of education carried out by the Principal has a positive effect and significant to changes in teacher performance. Teacher performance will be improved if Supervision of the principal's education in the form of leadership and supervision Improved.